Sampling Techniques Affect Mayfly Nymph Community Indices and May Bias Bioassessments - Yanai, Zohar; Dorchin, Netta (Insects (Basel, Switzerland), 2025)
Mayfly nymphs are reliable indicators of aquatic habitat quality, and whilst their presence and relative abundance are often used in bioassessment schemes, it is important to recognise that these attributes are affected by the sampling method employed. To test these effects, we sampled stream habitats for mayflies using two commonly used techniques in a standardised setup: aquatic sweep nets and manual collection from stones. These methods resulted in different success rates in detecting certain taxa depending on their biological traits (preferred microhabitat and locomotion type). Whilst species lists generally overlapped between the two methods, they yielded different values of total abundance, taxon richness, Shannon–Wiener’s diversity index, assemblage saprobic index, and general community structure. These results suggest that reliance on a single collection method is prone to yield only partial information for ecological assessments and emphasises the importance of employing a sampling technique that is appropriate for the study question and goals or combining more than one method. Based on these findings, we outline the scientific justifications for using each sampling method.